Epigenetic Modulation of Gene Expression from Quiescent Herpes Simplex Virus Genomes - Ferenczy, Michael W. (American Society for Microbiology (ASM), 2009)
The ability of herpes simplex virus to persist in cells depends on the extent of viral-gene expression, which may be controlled by epigenetic mechanisms. We used quiescent infection with the viral mutants d109 and d106 to explore the effects of cell type and the presence of the viral protein ICP0 on the expression and chromatin structure of the human cytomegalovirus (HCMV) tk and gC promoters on the viral genome. Expression from the HCMV promoter on the d109 genome decreased with time and was considerably less in HEL cells than in Vero cells. Expression from the HCMV promoter in d106 was considerably more abundant than in d109, and this increased with time in both cell types. The same pattern of expression was seen on the tk and gC genes on the viral genomes, although the levels of tk and gC RNA were approximately 10(2)- and 10(5)-fold lower than those of wild-type virus in d106 and d109, respectively. In micrococcal-nuclease digestion experiments, nucleosomes were evident on the d109 genome, and the amount of total H3 as determined by chromatin immunoprecipitation was considerably greater on d109 than d106 genomes. The acetylation of histone H3 on the d106 genomes was evident at early and late times postinfection in Vero cells, but only at late times in HEL cells. The same pattern was observed for H3 acetylated on lysine 9. Trimethylation of H3K9 on d109 genomes was evident only at late times postinfection in Vero cells, while it was observed both early and late in HEL cells. Heterochromatin protein 1γ (HP1γ) was generally present only on d109 genomes at late times postinfection of HEL cells. The observations of chromatin structure correlate with the expression patterns of the three analyzed genes on the quiescent genomes. Therefore, several mechanisms generally affect the expression and contribute to the silencing of persisting genomes. These are the abundance of nucleosomes, the acetylation state of the histones, and heterochromatin. The extents to which these different mechanisms contribute to repression vary in different cell types and are counteracted by the presence of ICP0.